The relationship between death anxiety and spiritual well-being in patients with gynecologic cancer - Kamyab Mansori, Yasmin; Dolatian, Mahrokh; Shams, Jamal; Nasiri, Maliheh (Advances in Nursing & Midwifery, 2018)
Background and Objectives: Concerns about death may negatively affect the health-related quality of life. The relationship between death anxiety and spiritual well-being in life-threatening diseases is still a matter that needs to be addressed, especially in patients with gynecologic cancer. This research was conducted to study the relationship between death anxiety and spiritual well-being in patients with gynecologic cancer. Materials and Methods: This descriptive-correlational study was conducted on 230 women with gynecologic cancer selected through convenience sampling from Shohada-e Tajrish Hospital, affiliated to Shahid Beheshti University of Medical Sciences, in Tehran, Iran, from April to May 2016. The data collection instruments included a demographic questionnaire, the 15-item Templer Death Anxiety Scale and the Spiritual Well-Being Scale. The data were analyzed in SPSS-22 using descriptive (mean, standard deviation, frequency and percentage) and inferential ( Pearson’s correlation coefficient and the linear regression model) statistics. Results: The average scores of death anxiety and spiritual well-being were 48.57±12.55 and 95.27±14/40. There was a significant relationship between death anxiety and spiritual well-being (r =-0.35, p=0.001). The results of the regression analysis showed that age (b=-0.23, p=0.001) and stage of cancer (b=-5.176, p=0.001) are the only significant predictors of death anxiety. This model explained 40.3% of the variance in death anxiety. In this model, age (b=0.220, p=0.021), marital status (b=2.985, p=0.043) and stage of cancer (b=2.649, p=0.001) were significant predictors of spiritual well-being. The model explained 18% of the variance in spiritual well-being in the patients. Conclusion: This study shows a significant relationship between death anxiety and spiritual well-being in patients with gynecologic cancer. It is therefore necessary for healthcare providers to address certain demographic variables such as age, marital status and disease progression for regulating death anxiety and improving the patients’ spiritual well-being.